ANALISIS SEMIOTIKA SAMPUL DEPAN MAJALAH TEMPO EDISI 9 – 15 MARET 2020 (KOMUNIKOLOGI : Jurnal Ilmiah Ilmu Komunikasi, 2020)
This study discusses the pandemic of covid-19 happened in Indonesia since March 2020. The government got spotlight from the public for their policy which has been taken to solve the pandemic through Tempo Magazine. Health Ministry is responsible side to take a policy to handle this case. Tempo Magazine  is a national  print media that  give a special attention to the government policy  toward covid-19 solution. This aims to reveal the message behind the meaning of Tempo Magazine  front cover by using semiotics analysis via Peirce model. This research method uses qualitative-descriptive approach. The result is message meaning from Tempo Magazine  front cover shows that the government is not ready yet to handle the covid-19 pandemic. There are  overlap policies between central and local government which caused the covid-19 pandemic unsolved well in Indonesia.Keywords: news of covid-19, magazine front cover, semiotics.